Brain Fluid Channels for Metabolite Removal - Maloveská, M; Humeník, F; Vikartovská, Z; Hudáková, N; Almášiová, V; Krešáková, L; Čížková, D (Physiological research, 2022)
The adult human brain represents only 2% of the body's total weight, however it is one of the most metabolically active organs in the mammalian body. Its high metabolic activity necessitates an efficacious waste clearance system. Besides the blood, there are two fluids closely linked to the brain and spinal cord drainage system: interstitial fluid (ISF) and cerebrospinal fluid (CSF). The aim of this review is to summarize the latest research clarifying the channels of metabolite removal by fluids from brain tissue, subarachnoid space (SAS) and brain dura (BD). Special attention is focused on lymphatic vascular structures in the brain dura, their localizations within the meninges, morphological properties and topographic anatomy. The review ends with an account of the consequences of brain lymphatic drainage failure. Knowledge of the physiological state of the clearance system is crucial in order to understand the changes related to impaired brain drainage.
Keywords: mícha; Humans; kinetika; savci; Brain; Spinal Cord; dospělí; lidé; Kinetics; Adult; Animals; mozek; zvířata; Mammals